1997
DOI: 10.1074/jbc.272.11.6903
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptionally Mediated Decreases in Folylpolyglutamate Synthetase Gene Expression in Some Folate Analogue-resistant Variants of the L1210 Cell

Abstract: L1210 cell variants resistant to edatrexate (EDX) were isolated by selection in vivo during therapy with this folate analogue. Among the variants selected, seven (L1210/EDX-4 to -7 and L1210/EDX-12 to -14) were found to exhibit 2-23-fold lower levels of folylpolyglutamate synthetase (FPGS) activity compared with parental L1210 cells. Lower levels of FPGS activity in cell-free extract from these variants using EDX as substrate were characterized by the same relative decrease in value for Biochemical alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Consistently, the mechanism that was identified in edatrexate-resistant L1210 leukemia cells was decreased rate of FPGS translation as judged from the poor translatability of the FPGS transcript in a cell-free translation system. 30 In the current study, we discovered another posttranscriptional alteration involving splicing defects in FPGS mRNA leading to loss of FPGS activity. However, whereas quantitative RT-PCR analysis, particularly with nondiagnostic PCR fragments, may frequently fail to identify such splicing defects, 14 Northern blot analysis proved instrumental in identification of changes in the full-length FPGS transcripts suggesting putative aberrant splicing ( Figure 4A); this was corroborated with diagnostic PCR analysis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Consistently, the mechanism that was identified in edatrexate-resistant L1210 leukemia cells was decreased rate of FPGS translation as judged from the poor translatability of the FPGS transcript in a cell-free translation system. 30 In the current study, we discovered another posttranscriptional alteration involving splicing defects in FPGS mRNA leading to loss of FPGS activity. However, whereas quantitative RT-PCR analysis, particularly with nondiagnostic PCR fragments, may frequently fail to identify such splicing defects, 14 Northern blot analysis proved instrumental in identification of changes in the full-length FPGS transcripts suggesting putative aberrant splicing ( Figure 4A); this was corroborated with diagnostic PCR analysis.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the latter further offers a novel molecular basis for the frequent emergence of tumor cells with antifolate-resistant phenotypes that display apparently normal FPGS mRNA levels commonly evaluated by RT-PCR analysis, while exhibiting loss of FPGS activity in the absence of inactivating point mutations. 5,10,13,14,17 In this respect, it has been frequently shown that loss of FPGS activity occurs in the absence of a parallel decrease in mRNA levels in multiple CCRF-CEM leukemia cells with acquired resistance to various polyglutamatable antifolates, 10,13,14,17,20 including MTX, 10,17,29 raltirexed, edatrexate, 30 or lometrexol (DDATHF). 13 This finding strongly suggested the existence of alterations at the posttranscriptional level of the FPGS gene.…”
Section: Discussionmentioning
confidence: 99%
“…In striking contrast, the CpG island surrounding P2 was completely unmethylated in all tissues studied, including normal and neoplastic tissues in which the P2 promoter was transcriptionally active (L1210 cells and marrow); liver, in which transcripts initiating at P2 were barely detectable; and brain, in which the entire fpgs gene was transcriptionally inactive (Table 1). Interestingly, the P2 promoter showed an unmethylated state starting from the position previously found to contain transcription factor binding sites controlling this promoter (17,61) and continuing until just before the second exon. We note that, over the differentially methylated P1, H3 and H4 acetylation correlates with transcriptional activity but, over the unmethylated CpG island-P2 promoter region, H3 and H4 acetylation and transcriptional activity were independent.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 [1][2][3][4][5][6][7] provides a summary of the key molecular features and clinical development status of the drugs reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…G3/4 toxicity (% of patients): neutropenia (21) increased transaminases(14), neurotoxicity (7), diarrhea (7), stomatitis (2), emesis(2).…”
mentioning
confidence: 99%